Single-phase formation mechanism and dielectric properties of sol-gel-derived Ba(Ti0.2Zr0.2Sn0.2Hf0.2Ce0.2)O3 high-entropy ceramics. (10th December 2022) - Liu, Jia; Ma, Cuiying; Wang, Lianli; Ren, Ke; Ran, Hongpei; Feng, Danni; Du, Huiling; Wang, Yiguang
Highlights: Single-phase BTZSHC high-entropy ceramics were successfully prepared via the sol-gel method at relative low temperature. The single-phase formation mechanism of the as-prepared high-entropy ceramics is attributed to thermodynamic factors. The sluggish diffusion effect ensures the thermal stability of high-entropy systems. The relaxor behavior of the BTZSHC high-entropy ceramics is caused by the thermal evolution of the PUs in the lattice. Abstract: Single-phase Ba(Ti0.2 Zr0.2 Sn0.2 Hf0.2 Ce0.2 )O3 (BTZSHC) high-entropy ceramics (HECs) with the perovskite structure were successfully prepared via the sol-gel method. The results reveal that the as-prepared ceramics exhibit a single cubic phase belonging to the P m 3 ¯ m space group. The high entropy is the driving force of the formation of single-phase ceramics. A larger entropy (Δ S mix ) and a negative enthalpy (Δ H mix ) are conducive to the formation of single-phase compounds. Herein, Δ S mix  = 0.323 R mole –1 and Δ H mix  = −43.88 kJ/mol. The sluggish-diffusion effect ensures the thermal stability of high-entropy systems. Dielectric measurements reveal that the as-prepared BTZSHC high-entropy ceramics are relaxor ferroelectrics, and the degree of relaxor ( γ ) is 1.9. The relaxor behavior of the as-prepared ceramics can be ascribed to the relaxation and thermal evolution of their polar units (PUs). The findings of this work provide a theoretical basis and technical support for the preparation of single-phase high-entropy ceramics.